Analysis of the microbiota associated with the blackening of activated sludge. (February 2021) - Huang, Xiaowu; Wei, Qiaoyan; Hong, Nian
Abstract: Activated sludge blackening is an alarming issue encountered during the operation of biological treatment processes, but the microbiota associated with the blackening of activated sludge remains unknown. 16S rRNA gene amplicon sequencing was applied to reveal the microbial community composition and dynamics of activated sludge experiencing the sludge blackening in this study. Surprisingly, microorganisms proliferated significantly in blackened sludge are not known to sulfur metabolism based on the information available. Functional profiles indicated that microbial communities of all 14 sludge samples have potential to reduce sulfate to sulfide. Genome annotation further validated microorganisms affiliated with Acidovorax and Mycolicibacterium were responsible for sulfide production in all samples. The homologues of Pseudomonas fluorescens, Janthinobacterium lividum, Hydrogenophaga intermedia, and Mycolicibacterium pulveris were potential active sulfide producer dominated the blackened sludge. This study revealed a more diverse sulfide producing microbial community unknown previously and further delineation of their metabolic versatilities including denitrification, sulfate reduction to sulfide, and thiosulfate oxidation to sulfate is necessary. Findings from this study suggested a broad role and contribution of these generalist microorganisms in regulating ecological sulfur-nitrogen-carbon transformation. Knowledge from such research offer in-depth understanding of the biochemical reaction responsible for sludge blackening and inspired novel research focuses on microbial-driven sulfur-nitrogen-carbon cycle. Graphical abstract: Image 1 Highlights: Diverse microorganisms previous unknown are responsible for sludge blackening. More indigenous microbiota of the activated sludge is implicated to producing sulfide. Diverse microbes are key players involving ecological S–N–C transformation.